Genetic mapping of the bacteriophage PS8 of Agrobacterium tumefaciens - Kubícková, D; Karpfel, Z; Bezdĕk, M (Folia microbiologica, 1979)
Genetic mapping of the chromosome of the bacteriophage PS8 of Agrobacterium tumefaciens using temperature sensitive (ts) mutants of the bacteriophage is described.
Keywords: Rhizobium; Chromosome Mapping; mapování chromozomů; Bacteriophages; bakteriofágy